Lattice doping regulated interfacial reactions in cathode for enhanced cycling stability - Lianfeng Zou (Nature Portfolio, 2019)
The electrode/electrolyte interface plays a critical role in a Li-ion battery. Here the authors report that Al doping can tailor the interfacial reactions to lead to enhanced structural stability and cyclability of cathode. Al dopants form not only lattice solid solution but also Al2O3 islands on the surface.